On the instability of lagrange solutions in the three-body problem - Sosnitskii, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We consider the relation between the Lyapunov instability of Lagrange equilateral triangle solutions and their orbital instability. We present a theorem on the orbital instability of Lagrange solutions. This theorem is extended to the planarn-body problem.